Energy crops - Halford, Nigel G.; Karp, A. (Royal Society of Chemistry, 2011)
The last few years have seen the concept of bioenergy and biofuels come of age. Rising oil prices have lead to more food crops being grown for energy as well as food. This has created controversy by adding to the upward pressure on crop commodity prices that was already being created by the increasing demand for food from an expanding population. More attention has, therefore, focussed on meeting the rising demand for bioenergy and biofuels in more sustainable ways. A wider range of crops is being explored, including non-food crops, as well as the use of crop residues rather than grain or seed.
Keywords: Energy crops.; elektronické knihy; electronic books